Rasch model analysis for Malaysian internet and sexual activities inventory - Hassan, Siti Aishah; Mohd Ayub, Ahmad Fauzi; Abu Bakar, Kaseh (Human Resource Management Academic Research Society, 2017)
Malaysian Internet and Sexual Activities Inventory (MISAI) was developed to measure individual differences in the tendency to be sexually preoccupied involvement using internet as a medium. We examined the psychometric properties of 23 items MISAI with sample size of 648 using the Rasch rating scales model. The results showed that the items of MISAI spreading covered a broad range of the latent continuum cybersex involvement. All items were functions in the same intended positive direction. Items appeared to unidimensionaly measure the severity of cybersex involvement. Items fit the Rasch model well, with low involvement in cybersex reliably proceeding to higher involvement in a potential progression toward increasing levels of severity of preoccupied involvement. All five responds categories were functioning from never true to always true indicating of the participants’ involvement in cybersex. The items fall within the infit and outfit cut-off values with an exception of one item. There were 55 misfit persons, yet the person and item showed high reliabilities. Scrutinizing the items and persons misfits, explanations are provided for practical use of this instrument and implications for future research direction, this paper are then suggested.